UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK MENGGUNAKAN PENDEKATAN CULTURALLY RESPONSIVE TEACHING PADA PESERTA DIDIK KELAS VII SMPN 5 SAMARINDA TAHUN AJARAN 2023/2024 - Aisyah Fitriani; Evie Palenewen (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The objective of this research is to improve students' mathematics learning outcomes using the Culturally Responsive Teaching (CRT) approach. For this study, Classroom Action Research (CAR) was conducted in two cycles. The Kemmis and Taggart model includes four stages: planning, action, observation, and reflection. The participants were 32 seventh-grade students from SMP Negeri 5 Samarinda. Essay-type questions were used to collect research data. Quantitative analysis was the data analysis method used. According to data analysis, the proportion of students meeting the mathematics learning objectives in Cycle I was 59.37%. In Cycle II, the success rate increased to 93.75%. The CRT approach provided meaningful learning experiences for seventh-grade students, incorporating cultural components and improving learning outcomes. Including cultural components can attract students and enhance their mathematics learning outcomes. This indicates that after using the CRT technique, the seventh-grade students of SMP Negeri 5 Samarinda achieved their mathematics learning objectives with improved learning outcomes.